2017
DOI: 10.1111/gcbb.12450
|View full text |Cite
|
Sign up to set email alerts
|

Hydrochar enhances growth of poplar for bioenergy while marginally contributing to direct soil carbon sequestration

Abstract: Hydrothermal carbonization (HTC) has been proposed as an alternative method to pyrolysis for producing C-rich amendments for soil C sequestration. However, the use of hydrochar (HC) as soil amendment is still controversial due to the limited information on the potential benefits and trade-offs that may follow its application into soil. This study investigated the effects of HC starting from maize silage on plant growth in a 2-year controlled experiment on poplar for bioenergy and evaluated HC stability in soil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…With regards to plant growth, Baronti et al (2017) found a significant increase in the biomass production of poplar trees with HC addition after two consecutive years, while Bargmann et al (2014b) showed no negative effects on spring barley at a 4% HC application rate. Furthermore, Schimmelpfennig et al (2014) saw a substantial reduction in plant growth with the field application of HC, particularly in the first year of the experiment.…”
Section: Introductionmentioning
confidence: 90%
“…With regards to plant growth, Baronti et al (2017) found a significant increase in the biomass production of poplar trees with HC addition after two consecutive years, while Bargmann et al (2014b) showed no negative effects on spring barley at a 4% HC application rate. Furthermore, Schimmelpfennig et al (2014) saw a substantial reduction in plant growth with the field application of HC, particularly in the first year of the experiment.…”
Section: Introductionmentioning
confidence: 90%
“…Studies showed that the response to application of carbonaceous materials, as hydrochar and biochar, to the soil depends not only on the biomass used in the thermochemical conversion process, but also on the reaction parameters applied [29][30][31][32][33]. Furthermore, these responses may be linked to hydrochar application rates [34], time after the application to the soil [35], and treatment carried out on hydrochar prior to this soil application [36,37]. Positive results have been reported after 2 years from hydrochar soil application showing an improvement in biomass production [35], and also from pre-treated co-composted hydrochar used for plant growth, whatever the feedstock used to produce hydrochar.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, these responses may be linked to hydrochar application rates [34], time after the application to the soil [35], and treatment carried out on hydrochar prior to this soil application [36,37]. Positive results have been reported after 2 years from hydrochar soil application showing an improvement in biomass production [35], and also from pre-treated co-composted hydrochar used for plant growth, whatever the feedstock used to produce hydrochar. Best results were found for hydrochar treated with maize silage digestate and anaerobic fermentation, when compared to untreated hydrochar [38].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies reported adverse impacts of hydrochar derived from beet root chips on plant productivity and seed germination even when applied as low as 20-25% of volume of the growth mixture [33,34]. However, other studies offered contradictory findings about the effects of hydrochar on a fast-growing tree species: Baronti et al [35] and George et al [27] showed that biomass productivity and nitrogen use efficiency increased in poplar tree seedlings treated with hydrohar derived from maize (Zea mays L.) silage feedstock. These contradictory results concerning the effects of hydrochar on plant productivity call for careful choice of feedstock, application rate and the target species to ensure optimum growth benefits.…”
Section: Introductionmentioning
confidence: 99%